2020
DOI: 10.1002/2050-7038.12356
|View full text |Cite
|
Sign up to set email alerts
|

Optimized reactive power support strategy for photovoltaic inverter to intensify the dynamic voltage stability of islanded microgrid

Abstract: Summary This study presents an innovative and optimized reactive power support (ORPS) strategy for photovoltaic (PV) inverters to improve the dynamic voltage stability (DVS) of islanded microgrid (MG) with induction motor (IM) load. On the occurrence of the fault, voltage instability (VI) happens due to the low‐inertia IM load and poor ride through capability of PV inverters of MG. Supplement of optimal RPS promptly, without exceeding the rated current value of the inverter, is aimed at the proposed control, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Many voltage support strategies for grid-connected IBGs have been reported in the literature, such as [19][20][21][22]. Enhancing voltage stability of islanded MGs with voltage support is reported in [23,24]. To mitigate the voltage instability of islanded MGs, prioritized reactive current injection from the inverter has been presented as a means for voltage support.…”
Section: Microgrid Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many voltage support strategies for grid-connected IBGs have been reported in the literature, such as [19][20][21][22]. Enhancing voltage stability of islanded MGs with voltage support is reported in [23,24]. To mitigate the voltage instability of islanded MGs, prioritized reactive current injection from the inverter has been presented as a means for voltage support.…”
Section: Microgrid Configurationsmentioning
confidence: 99%
“…The network-load admittance ratio is in terms of the power network admittance matrix and the equivalent admittances of net loads, and the effects of constant-power and constant-current DGs are taken into consideration. Equation (24) gives a voltage stability index, M n/d under the condition that the power flow Jacobian is singular if, and only if, the network-load admittance ratio is unity, i.e., R n/d = 1.…”
Section: Network-load Admittance Ratio-based Vsimentioning
confidence: 99%
“…In conventional power systems, this happens with reactive power injection predominantly because of negligible resistive line parameters [15]. Therefore, conventionally the VS strategy with constant peak current control has been designed to focus on the precedence of reactive current [16], [17], [18]. In the conventional strategy, the active current is considered as a subordinate component and decreased to increase the reactive current injection.…”
Section: Introductionmentioning
confidence: 99%
“…7,[15][16][17][18][19][20][21] In contrast, very few studies have focused on the short-term voltage stability, which is also known as dynamic voltage stability. [22][23][24][25][26][27][28] In Reference 22, the authors have investigated the impacts of LVRT by PV inverters on the DVS, and concluded that DVI is likely to occur in highly PV penetrated power systems after a severe fault if the PV inverters are incapable of providing the LVRT. In Reference 25, a new control strategy has been proposed with PV units to improve the DVS.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to reveal that numerous research have been conducted to contribute in better understanding of the long‐term voltage instability caused by large PV integration 7,15‐21 . In contrast, very few studies have focused on the short‐term voltage stability, which is also known as dynamic voltage stability 22‐28 . In Reference 22, the authors have investigated the impacts of LVRT by PV inverters on the DVS, and concluded that DVI is likely to occur in highly PV penetrated power systems after a severe fault if the PV inverters are incapable of providing the LVRT.…”
Section: Introductionmentioning
confidence: 99%